Cattle immunized against the pathogenic l-α-glycerol-3-phosphate oxidase of Mycoplasma mycoides subs. mycoides in cattle fail to generate neutralizing antibodies and succumb to disease on challenge - Mulongo, Musa M.; Frey, J.; Smith, K.; Schnier, C.; Wesonga, H.O.; Naessens, Jan; McKeever, Declan J. (Elsevier, 2013)
The membrane-associated enzyme l-α-glycerol-3-phosphate oxidase (GlpO) of Mycoplasma mycoides subs. mycoides (Mmm), the causal agent of contagious bovine pleuropneumonia (CBPP) has been identified as a virulence factor responsible for the release of toxic by-products such as H2O2 that mediate host cell injury. Since CBPP pathogenesis is based on host inflammatory reactions, we have determined the capacity of recombinant GlpO to generate in vivo protective responses against challenge in immunized cattle. We also investigated whether sera raised against recombinant GlpO in cattle and mice inhibit production of H2O2 by Mmm. Immunization of cattle with recombinant GlpO did not protect against challenge with a virulent strain of Mmm. Further, although both murine and bovine antisera raised against recombinant GlpO detected recombinant and native forms of GlpO in immunoblot assays with similar titres, only murine antibodies could neutralize GlpO enzymatic function. The data raise the possibility that Mmm has adapted to evade potential detrimental antibody responses in its definitive host.